2018
DOI: 10.1021/acs.analchem.8b01834
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Protein O-Glycosylation: Solid-Phase Chemoenzymatic Cleavage and Enrichment

Abstract: Glycosylation plays a critical role in the biosynthetic-secretory pathway in the endoplasmic reticulum (ER) and Golgi apparatus. Over 50% of mammalian cellular proteins are typically glycosylated; this modification is involved in a wide range of biological functions such as barrier formation against intestinal microbes and serves as signaling molecules for selectins and galectins in the innate immune system. N-linked glycosylation analysis has been greatly facilitated owing to a range of specific enzymes avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 43 publications
0
102
0
Order By: Relevance
“…OpeRATOR, identified from the mucin degrading human intestinal bacterium Akkermansia muciniphila , recognizes O‐linked glycans and cleaves O‐linked glycopeptides at the N‐termini of O‐linked glycan‐occupied Ser or Thr to release site‐specific O‐linked glycopeptides with their conjugated O‐linked glycans. During the peer‐review period of our study, a manuscript by Yang et al (), described the analysis of O‐linked glycosylation sites from several simple glycoproteins including fetuin, mucin, and Zika viral proteins. This study took use of the enzyme, OpeRATOR, with cleavage of peptide sequences at the N‐termini of the O‐linked glycosylation sites (Yang et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OpeRATOR, identified from the mucin degrading human intestinal bacterium Akkermansia muciniphila , recognizes O‐linked glycans and cleaves O‐linked glycopeptides at the N‐termini of O‐linked glycan‐occupied Ser or Thr to release site‐specific O‐linked glycopeptides with their conjugated O‐linked glycans. During the peer‐review period of our study, a manuscript by Yang et al (), described the analysis of O‐linked glycosylation sites from several simple glycoproteins including fetuin, mucin, and Zika viral proteins. This study took use of the enzyme, OpeRATOR, with cleavage of peptide sequences at the N‐termini of the O‐linked glycosylation sites (Yang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…During the peer‐review period of our study, a manuscript by Yang et al (), described the analysis of O‐linked glycosylation sites from several simple glycoproteins including fetuin, mucin, and Zika viral proteins. This study took use of the enzyme, OpeRATOR, with cleavage of peptide sequences at the N‐termini of the O‐linked glycosylation sites (Yang et al , ). However, the glycan specificity and cleavage specificity for the O‐linked glycosylation sites by OpeRATOR enzyme are not clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Systems with truncated forms of glycosylation, such as engineered "SimpleCells" lacking O-glycan elaboration machinery can simplify mucin analysis and glycosite identification, but functionally important glycan structures beyond the initiating O-GalNAc are lost (26). Recently, an "O-protease" was reported that cleaves N-terminally to glycosylated serine and threonine residues (27,28). However, this enzyme requires substrate desialylation for optimal activity, and is not specific for mucins.…”
mentioning
confidence: 99%
“…The enzyme, OpeRATOR, appears to be broadly active on O‐glycosylation sites occupied by multiple core types. It generates a new N‐terminus by cleavage of the peptide bond between the occupied Ser or Thr and its N‐terminal amino acid residue (Yang et al, 2018a, c). The enzyme has been used successfully to investigate Zika virus envelope E and NS‐1 proteins (Yang et al, 2018a).…”
Section: Mass Spectrometry Pathways To Meaningful Glycomics Datamentioning
confidence: 99%